Conformationally Preorganized Diastereomeric Norbornane-Based Maltosides for Membrane Protein Study: Implications of Detergent Kink for Micellar Properties - Das,M; Du,Y; Ribeiro,O; Hariharan,P; Mortensen,JS; Patra,D; Skiniotis,G; Loland,CJ; Guan,L; Kobilka,BK; Byrne,B; Chae,PS (Journal of the American Chemical Society, 2017)
Detergents are essential tools for functional and structural studies of membrane proteins. However, conventional detergents are limited in their scope and utility, particularly for eukaryotic membrane proteins. Thus, there are major efforts to develop new amphipathic agents with enhanced properties. Here, a novel class of diastereomeric agents with a preorganized conformation, designated norbornane-based maltosides (NBMs), were prepared and evaluated for their ability to solubilize and stabilize membrane proteins. Representative NBMs displayed enhanced behaviors compared to n-dodecyl-β-d-maltoside (DDM) for all membrane proteins tested. Efficacy of the individual NBMs varied depending on the overall detergent shape and alkyl chain length. Specifically, NBMs with no kink in the lipophilic region conferred greater stability to the proteins than NBMs with a kink. In addition, long alkyl chain NBMs were generally better at stabilizing membrane proteins than short alkyl chain agents. Furthermore, use of one well-behaving NBM enabled us to attain a marked stabilization and clear visualization of a challenging membrane protein complex using electron microscopy. Thus, this study not only describes novel maltoside detergents with enhanced protein-stabilizing properties but also suggests that overall detergent geometry has an important role in determining membrane protein stability. Notably, this is the first systematic study on the effect of detergent kinking on micellar properties and associated membrane protein stability.